2009
DOI: 10.1017/s0021859609990165
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprinting of lamb and beef production systems: insights from an empirical analysis of farms in Wales, UK

Abstract: SUMMARYCarbon footprinting is an increasingly important method of communicating the climate change impacts of food production to stakeholders. Few studies utilize empirical data collected from farms to calculate the carbon footprints of lamb and beef. Data from two farms in Wales, UK, were employed to undertake such an analysis for two system boundaries.Within a system boundary that considers the embodied greenhouse gases (GHGs) in inputs and on-farm emissions, producing 1 kg of lamb releases 1·3–4·4 kg CO2 eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 25 publications
4
36
1
Order By: Relevance
“…All LCA input data were normalized to this per head of swine unit of measure. Study results using our per head of swine functional unit are comparable to other commonly used functional units, such as kg of pork produced leaving the facility (Basset-Mens and van der Werf, 2005;Eriksson et al, 2005;Edwards-Jones et al, 2009) by dividing our results by net pig growth (89 kg), or kg of hot standard carcass (Peters et al, 2010) by dividing our results by net pig growth times 0.74.…”
Section: Functional Unitsupporting
confidence: 56%
See 2 more Smart Citations
“…All LCA input data were normalized to this per head of swine unit of measure. Study results using our per head of swine functional unit are comparable to other commonly used functional units, such as kg of pork produced leaving the facility (Basset-Mens and van der Werf, 2005;Eriksson et al, 2005;Edwards-Jones et al, 2009) by dividing our results by net pig growth (89 kg), or kg of hot standard carcass (Peters et al, 2010) by dividing our results by net pig growth times 0.74.…”
Section: Functional Unitsupporting
confidence: 56%
“…For example, Edwards- Jones et al (2009) reported that methane enteric emissions from sheep and cattle (708.8 to 2308.1 CO 2 eq/ha/year) were significantly higher than manure emissions (25.9 to 79.5 CO 2 eq/ha/year). Peters et al (2010) also reported that the primary source of GHG emissions was enteric methanogenesis for their study of Australian red meat production (0.18 kg CH 4 / head of cattle/day) and that 38% reduction of enteric methane emissions occurred when utilizing grain instead of grass feed.…”
Section: Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…As an important source of emissions, the agricultural sectors in England and Wales are required to contribute to the UK commitment of reducing total national GHG emissions by 80% by 2050 (from 1990 levels) under the Climate Change Act 2008 (DECC, 2011). Agricultural emissions are dominated by methane (CH 4 ) emitted largely as a by-product of feed fermentation in ruminant animals, and nitrous oxide (N 2 O) primarily produced from soils in response to fertiliser application and excreta deposition (Edwards-Jones et al, 2009;Salisbury et al, 2013). The first and last of these can be primarily attributed to ruminant livestock production.…”
Section: Introductionmentioning
confidence: 99%
“…), and thus the carbon footprint per kilogram of output is considerably higher compared to more intensive production systems (Edwards‐Jones et al. ; Gill et al. ).…”
Section: Use Of Natural and Semi‐natural Grasslandsmentioning
confidence: 99%